Total Phenolic Content and Antioxidant Activity of Cereal Bran Enriched Ready to Eat Breakfast Cereal Porridge - Sharma, Savita; Dar, B. N.; Nayik, G. A.; Kaur, Gurkirat (Current Nutrition & Food Science, 2016)
Background: In the current study, porridges were analyzed for antioxidant properties (total phenolic content-TPC, DPPH radical scavenging activity-DPPH-RSA and Trolox equivalent antioxidant capacity-TEAC) extracted with acetone, methanol and hexane under conventional and microwave assisted extraction. Methods: Two extraction methods (traditional and microwave assisted) with different solvents (acetone, hexane and methanol) were followed for potential extraction of antioxidants. Results: The effect of system solvents and different types of brans employed for the precise quantification of antioxidant properties showed that for various types of bran enriched porridge; methanol gave the highest yield of total phenolic content followed by acetone and hexane under both extraction methods. The level of supplementation of brans increased the total phenolic content of porridge significantly (P≤0.05). Methanolic extracts of all cereal bran enriched porridge showed the highest values for percent inhibition of DPPH-RSA. With the ABTS method (TEAC), wheat bran enriched methanolic extracts showed the highest values (up to 8.88 TEμmole/g). Conclusion: Bran enriched porridge showed high phenolic content having high antioxidant activity, which could be serve a potential ingredient for consumer health. Moreover, methanol was found to be effective in solvent extraction of phenolic compounds.
Keywords: Cereal brans